Structural relations amongst religiosity, self-control, and externalizing problems of juveniles in Malaysia - Mohd Kadri, Nursyuhaidah; Zulkefly, Nor Sheereen; Baharudin, Rozumah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Early onset of externalizing behaviour may increase the likelihood of extensive maladaptation in future life. Recently, there has been a growing research undertaken on the role of religiosity on externalizing behaviour among Muslim adolescents. However, the mechanism underlying this relationship is still poorly understood. This study sets out to examine the relationships between adolescent religiosity, self-control, and externalizing behaviours (rule-breaking and aggressive behaviours) of Muslim juveniles in rehabilitation centre. Methods: Questionnaire assessments of adolescent religiosity, self-control, rule-breaking behaviour, and aggressive behaviour were collected from 427 Muslim adolescents aged between 13 to 18 years old in eight Tunas Bakti Schools (STB). Results: Structural equation modeling analysis indicated adolescent religiosity was negatively associated with externalizing behaviour, both directly and indirectly. The indirect association was mediated by self-control. This study suggests that greater adolescent religiosity was associated with higher self-control, which in turn lowers both rule-breaking and aggressive behaviour. Conclusion: The results highlight the important role of religiosity and self-control in preventing externalizing behaviour among Muslim adolescents. Further step towards designing preventative strategy may need to consider integrating both Islamic-based program and self-control input to enhance mental health and behavioural adjustment of Muslim adolescents.